Valoración de la masa grasa en futbolistas jóvenes de alto rendimiento: comparación de métodos antropométricos con absorciometría dual de rayos X (DEXA) - Garcia, N.; Zapata, D.; Saez, C.; Yanez, R.; Penailillo, L. (Archivos de medicina del deporte, 2015)
There are multiple anthropometric equations described in the literature to estimate the body fat mass, but there are some variations between them, with no consensus on which one is the best equation for estimating fat mass for specific populations. The aim of this study was to compare the percentages of body fat mass obtained from anthropometric equations commonly used to estimate body fat, with dual X-ray absorptiometry (DEXA) as gold standard, in young Chilean elite soccer players. 43 soccer players from young national teams were assessed (age: 16.9 ± 1.3 y). The percentage of body fat using nine equations was estimated and compared with the percentage of fat obtained from DEXA. The percentage of body fat estimated by the anthropometric equations from Faulkner (11.1 ± 1.6%) and Slaughter (11.5 ± 3.2%), plus body density equations (and fat mass estimated through Brozek equation) from Wilmore & Behnke (11.7 ± 1.7%), Jackson & Pollock (11.8 ± 3.7%), Durnin & Womersley (12.9 ± 2.9%) and Withers (10.4 ± 2.5%) showed no significant difference with the measurement performed with DEXA (12.9 ± 4 1%). Of these, the equation of Durnin & Womersley, showed less inter-method difference with DEXA (0.06 ± 2.0%), although no significant differences with inter-method differences from the equations of Slaughter (-1.3 ± 2.5%), Wilmore & Behnke (-1.2 ± 3.0%) and Jackson & Pollock (-3.6 ± 2.8%) were found. The correlations of the equations with DEXA measurement showed that the Spearman coefficient resulted between 0.45 and 0.88, all statistically significant. In conclusion, the equations of Durnin & Womersley, Slaughter, Wilmore & Behnke and Jackson & Pollock are those that come closest to the reference method to be used in young soccer players.